Pulmonary Artery Pseudoaneurysm: A Rare Cause of Hemoptysis in a Child - Vaideeswar, Pradeep; Karande, Sunil; Yadav, Subhash; Pardeshi, Kirti (Pediatric and developmental pathology, 2016)
Aneurysms and pseudoaneurysms of pulmonary vasculature are uncommon occurrences that contribute to mortality and morbidity, without timely diagnosis and intervention. We report a fatal massive hemoptysis in a child due to a consolidation-related pulmonary arterial pseudoaneurysm, an extremely rare phenomenon.